The prerequisites for developing club abilities in rhythmic gymnastics based on the coordination requirements of the routines - Suprun, A. A.; Terekhina, R. N.; Ozhiganova, A. S.; Lunina, I. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to provide a scientific foundation for the development of subject skills in rhythmic gymnastics, in accordance with the coordination profile of the exercises.